Exploring the Male Gaze and Power Relations in Tracy Chevalier’s Girl with a Pearl Earring - Ala Beshank Ahmed; Meram Salim Shekh Mohamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The interwoven relationship between art and literature is exemplified in the eminent novel Girl with a Pearl Earring by Tracy Chevalier (1999). This novel is inspired by the painting with the same title, created by Johannes Vermeer (1665-1666). The artwork serves as a visual narrative, sparking literary interpretations and inspiring various written works. The mysterious gaze of the girl in the painting, coupled with the subtle play of light, has prompted writers to craft stories, poems, and novels, examining the imagined life and emotions of the subject. This article investigates the novel by focusing on the connections between the painting and the narration, each form enriches and complements the other in a harmonious blend of creativity. It will discuss how intertextuality is presented by applying Julia Kristeva’s theory, as well as highlighting the main character's victimization of the male gaze as discussed by Laura Mulvey’s psychoanalyst interpretations. This paves the way to illustrating the power relations between a master and a maid through Micheal Foucault’s theories